Thermogravimetric investigations of nasal gel with diltiazem - L. K. Kuchina; V. V. Gladyshev; I. A. Puchalskaya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. To conduct the thermogravimetric investigations of nasal gel with diltiazem.